A stairway to heaven: daoist self-cultivation in early modern China - van Enckevort, Paul (Sinica Leidensia Series, 2025)
First book-length, English-language study of the life and works of Wu Shouyang, the perhaps most important master and author of Daoist self-cultivation and inner alchemy texts in early modern China.